Melanin in the Retinal Epithelium and Magnetic Sensing: A Review of Current Studies - Lidia Zueva; Vassiliy Tsytsarev; Janaina Alves; Mikhail Inyushin (Biophysica)
Coming in a variety of forms, melanin is one of the most abundant, stable, diverse, and evolutionarily ancient pigments found in living things in nature. These pigments often serve protective functions, typically well-adapted to their specific roles. One such protective function is metal chelation and cation exchange, which help regulate and buffer metal concentrations within cells. By binding to certain metals, melanin can acquire magnetic properties. Because of this, it may play a role in magnetic effects and possibly in the response of organisms to external magnetic fields and magnetic sensing. While there is melanin in plants, microbes, fungi, and invertebrates, certain types of melanin are specifically associated with the retina in vertebrates, including migrating bird and fish species. In this review, we examine studies focusing on the properties of melanin in these parts of the body and their possible association with magnetic sensing, and generally, magnetic sensing in the retina.